(untitled) (Journal of Forest and Livelihood, 2004)
The Community Forests Management approach in Nepal is one of the most cited success stories for managing common property resources. It has been argued that the approach is successful in improving the supply of forest products, improving the environmental situation in the hills, rehabilitating degraded hills and also increasing biodiversity. It is claimed that the approach offers an attainable means to conserve the biodiversity of Nepal. However, the prevalent management approach in community forestry indicates increasing threats to the conservation of biodiversity. This paper is based on the findings from two community forest users groups from the middle hills of Nepal and argues that the prevalent forest management approach in community forestry recognizes biodiversity conservation as secondary issue and there is evidence that biodiversity has either declined or has been altered in community managed forest.